Perspectives of incarcerated women on risk factors for sexually transmitted infection - Araújo de Carvalho, Iêda (2020)
Objective: to know the perspectives of incarcerated women on the risk factors for sexually transmitted infections. Method: This is an exploratory and qualitative study, carried out in a female public channel in the mid-north region of Mato Grosso, Brazil, in November 2019. The data collection was carried out through an interview with 53 women. For data analysis, IRAMUTEQ version 0.7 software was used, which presents similarity graphs. Result: The results show that there are factors that go beyond the scope of individual resources for self-care, which hinder preventive actions, such as architectural conditions and disciplinary rules in prison. These environmental peculiarities impose other factors that increase the risk of sexually transmitted infections, such as difficulty in cleaning clothes and shared use of the bathroom. Conclusion: Therefore, strategies that unite the needs of these women with the inherent risks and added to the prison reality are presented as a favorable way for the prison to stop being only a space of recrudescence, and for custody to be fulfilled. the generation of new people, with the recovery of dignity. and awareness / conditions for self-care against infections and other health problems.